Emotions and Crime over the Life Course: A Neo-Meadian Perspective on Criminal Continuity and Change - Cernkovich, Stephen A. (2007)
A symbolic interactionist perspective on the emotions is presented that highlights their social character, forges links to cognitive processes, and suggests ways in which emotions influence long-term patterns of criminal involvement. This neo-Meadian perspective contrasts with theories of desistance that focus on the role of informal social controls and develops the view of an emotional self that flourishes somewhat independent of the major role transitions typically emphasized in sociological studies of the life course. The authors also explore ways in which attention to the emotional realms of experience adds to traditional treatments of the impact of adult transition events ( e. g., the good marriage effect ). Interviews with male and female adolescent offenders and two waves of adult follow-u data document general patterns of association and support the argument that a social view of emotional processes is critical to a comprehensive understanding of life course patterns of criminal continuity and change